Custos da qualidade: uma investigação da prática e percepção empresarial - Collaziol, Elisandra (Universidade do Vale do Rio do Sinos, 2006)
This research aims at investigating the effective of accountancy practices on the measurement of Quality of Costs (COQ), as well as evaluating the perception of managers about the utility of it. Furthermore, the research tries to verify the understanding of certifying companies concerning the compulsoriness of measurement of COQ by companies ISO which have been certified. The population is formed by companies certified by the ISO 9000: 2000 series that are in the files of the Gaucho Program of Quality and Productivity (PGQP) in the region of Porto Alegre and also of certifying companies accredited by INMETRO. This research is exploratory and descriptive as for its aims, qualitative and quantitative as for the approach of the problem and a survey as for the technical procedures and a questionnaire for data collecting. For the data analysis the descriptive statistic and factor analyses have been used. About the results, it has been verified the non- compulsoriness of the measurement of cost for the certificatio
Keywords: certificação; percepção; qualidade; custos; certification; perception; quality; cost; Ciências Sociais Aplicadas